Structural Alteration of Motor and Sensory Cortices in Parkinson's Disease Using Magnetic Resonance Imaging: Automatic Brain Segmentation - Shareef, Sahar; Ali, Tahir; Sahin, Bunyamin; Elfaki, Amani; Mohammad, Raeesa Abdel Tawab; Ahmed, Aly Mohamed; Atteya, Muhammad (Inst Advanced Science Extension, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder commonly diagnosed as motor triad of symptoms including tremor, rigidity and bradykinesia. The degeneration of the Substantia nigra in PD, leads to alterations in the function of cortical areas including primary motor cortex and other non-primary motor areas. The combination of motor and sensory symptoms marked in PD, is the cause of investigating the structural changes of motor and sensory cortices in PD. The aim of this study is to detect the structural changes of cortical thickness and the volume of grey matter and white matter in motor and sensory cortices in PD. This will help in early detection of the disease, monitor response to medication or help in prognosis and prediction of outcomes. Nineteen control volunteers and 18 Parkinson's patients were participated in the study. The ages of participants were ranging between 45-65 years (mean 56.14 years). Structural magnetic resonance imaging was performed and the Digital Imaging and Communications in Medicine (DICOM) images were evaluated using automatic brain segmentation software (BrainSuite). The structural changes in the present study were found in the thickness of the motor cortex and in the volume of grey matter (GM) of the sensory cortex. The thickness of the right motor cortex for males was smaller in Parkinson's patients than control. The volume of the GM of left sensory cortex for males was smaller in Parkinson's patients than control. While no differences were found between Patients and controls in the volume of GM or white matter (WM) in the motor cortex, or in the volume of WM and the cortical thickness in the sensory cortex. Structural changes in specific areas of the brain may influence specific symptoms. (C) 2018 The Authors. Published by IASE.
Keywords: MRI; Parkinson's Disease; Automatic Brain Segmentation